GESTIÓN DEL TALENTO HUMANO EN INDUSTRIAL PAPELERA ECUATORIANA S.A - Baños Leon, Jorge Luis (2019)
The human talent is the fundamental part of the companies and of any daily activity of the same, so it is important to be aware of each of the problems that Industrial Papelera Ecuatoriana SA has, through information and observation of the circumstances that occur within it. The procedures that have made possible the low productivity and deficiency in several aspects, specifically those related to communication and labor relations among workers who are those who are performing the frequent tasks of the company; or with their heads and superiors, who are the ones who train, train, recruit and establish precepts for the operation of the entity, taking into account external regulations and political, social, environmental, cultural and economic factors